Thioxanthone disulfide-modified PCL macrophotoinitiator: Synthesis, characterization, and application in photoinduced PCL-b-PMMA block copolymer formation - Kazancioglu, Elif Ozcelik; Sariyildiz, Eyup Ensar; Arsu, Nergis (ELSEVIER SCIENCE SA, 2025)
PCL-[TX-S]2-PCL was synthesized via the successful ring-opening polymerization of epsilon-caprolactone, using Sn (Oct)2 as a catalyst in the presence of the TX-based disulfide derivative [OH-TX-S]2 and utilized as a macrophotoinitiator for the photoinduced polymerization of methyl methacrylate (MMA), for the formation of PCL-TXS-PMMA copolymers containing a photoactive thioxanthone unit. The synthesized PCL polymer and copolymers are notable for their biodegradability and low toxicity, as they are derived from poly(epsilon-caprolactone). Steadystate absorption and excited-state fluorescence emission studies characterized the mid-chain TX unit in PCL[TX-S]2-PCL polymer and the PCL-TX-S-PMMA copolymers. Differential scanning calorimetry (DSC) was employed to analyze the thermal properties of the copolymers, specifically their melting and crystallization temperatures, and found that Tm and Tg values were in harmony with those given in the literature. PCL-[TX-S]2PCL was also used to fabricate nanocomposite thin films consisting of in-situ formed Ag nanoparticles (AgNps) through the simultaneous polymerization of 2-hydroxyethyl acrylate (HEA). These findings will significantly contribute to developing a new generation of biocompatible complex macromolecular structures with controlled reactivity and versatile applications.
Keywords: Macrophotoinitiator; Poly(epsilon-caprolactone); Dynamic disulfide bond; Block copolymer; thioxanthone; MIDCHAIN FUNCTIONAL MACROPHOTOINITIATORS; FREE-RADICAL POLYMERIZATION; CHAIN; PHOTOINITIATORS; MOIETIES; ROP; Chemistry; Materials Science